2019
DOI: 10.14349/rlp.2019.v51.n3.6
|View full text |Cite
|
Sign up to set email alerts
|

The increase in emotional symptoms of novice clinical psychology trainees compared with a control cohort

Abstract: Cross-sectional research has shown that clinical psychology trainees usually face a wide range of stressors related to the clinical practice and tend to present higher distress than other psychology students. However, to our knowledge, no longitudinal study has been conducted analysing this fact. Specifically, this study analyses the evolution of emotional symptoms among a group of novice clinical psychology trainees compared with a control cohort. We recruited 575 Colombian Psychology undergraduates: 52.9% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Thompson et al (2005) have proposed that, forgiveness is a coping process enabling individual to resolve the distress induced by events that violate their assumptions, by turning their attention away from these adverse life experiences. Previous study has found that repetitive negative thinking focused on the clinical practice longitudinally predicted the increase of emotional symptoms among novice clinical trainee (Ruiz et al, 2019). To some extent, forgiveness is a form of willing to accept the negative events; it is a sign as psychological flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al (2005) have proposed that, forgiveness is a coping process enabling individual to resolve the distress induced by events that violate their assumptions, by turning their attention away from these adverse life experiences. Previous study has found that repetitive negative thinking focused on the clinical practice longitudinally predicted the increase of emotional symptoms among novice clinical trainee (Ruiz et al, 2019). To some extent, forgiveness is a form of willing to accept the negative events; it is a sign as psychological flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…In Study 2, a group of 41 clinical psychology trainees was asked to rate the DAC components in terms of perceived clarity and utility. These ratings were obtained during the trainees' participation in a randomized controlled trial that analyzed the effect of the DAC program components in preventing the common increase of emotional symptoms in novice clinical psychology trainees ( Ruiz, Dereix-Calonge, & Sierra, 2019 ). The DAC program was administered through six group sessions or workshops ( Dereix-Calonge et al, 2019 ).…”
Section: Aims Of This Studymentioning
confidence: 99%
“…This sample was recruited to participate in a randomized controlled trial that served as a preliminary evaluation of the effect of DAC's components on emotional symptoms and valued living among novice clinical psychology trainees ( Dereix-Calonge et al, 2019 ). The rationale for piloting DAC's components with this population was based on previous studies that found that (a) similar novice clinical psychology trainees showed a significantly higher increase in emotional symptoms throughout the semester than a control cohort ( Ruiz, Dereix-Calonge, & Sierra, 2019 ), and (b) RNT focused on the clinical practice longitudinally predicted the changes in their emotional symptoms ( Dereix-Calonge et al, 2020 ).…”
Section: Study 2: Analyzing the Content Validity And Perceived Utilit...mentioning
confidence: 99%
“…Many professions and disciplines have written about the anxiety that students experience when they do their first practical placement (Bischoff et al, 2002; Beilock & Carr, 2001; Decker et al, 2019; Jordan et al, 2020; Kenny, 2005; May, 2015; Ruiz, Derux-Calonge & Sierra, 2019; Simpson & Sawatzky, 2020; Tarrasch, 2019; Wagas et al, 2015). Nevertheless, spiritual care and psycho-spiritual therapy lack such research.…”
Section: Origins Of Performance Anxietymentioning
confidence: 99%